Critical role of CDK11p58 in human breast cancer growth and angiogenesis. Issue 1 (December 2015) - Chi, Yayun; Huang, Sheng; Peng, Haojie; Liu, Mengying; Zhao, Jun; Shao, Zhiming; Wu, Jiong
Abstract Background A capillary network is needed in cancer growth and metastasis. Induction of angiogenesis represents one of the major hallmarks of cancer. CDK11p58, a Ser/Thr kinase that belongs to the Cell Division Cycle 2-like 1 (CDC2L1) subfamily is associated with cell cycle progression, tumorigenesis, sister chromatid cohesion and apoptotic signaling. However, its role in breast cancer proliferation and angiogenesis remains unclear. Methods Tumorigenicity assays and blood vessel assessment in athymic mice were used to assess the function of CDK11p58 in tumor proliferation and angiogenesis. CCK-8 assay was used to detect breast cancer cell growth. Immunohistochemistry was used to detect the expression of vascular endothelial growth factor (VEGF), CD31 and CD34 in CDK11 positive patient breast cancer tissues. Dual-Luciferase array was used to analyze the function of CDK11p58 in the regulation of VEGF promoter activity. Western blot was used to detect related protein expression levels. Results CDK11p58 inhibited breast cancer growth and angiogenesis in breast cancer cells and in nude mice transplanted with tumors. Immunohistochemistry confirmed that CDK11p58 was negatively associated with angiogenesis-related proteins such as VEGF, CD31 and CD34 in breast cancer patients. Real-time PCR and dual-luciferase assay showed CDK11p58 inhibited the mRNA levels of VEGF and the promoter activity of VEGF. As CDK11p58 is a Ser/Thr kinase, the kinase-dead mutant failed to inhibit VEGF mRNA and promoter activity. Western blot analysis showed the same pattern of related protein expression. The data suggested angiogenesis inhibition was dependent on CDK11p58 kinase activity. Conclusion This study indicates that CDK11p58 inhibits the growth and angiogenesis of breast cancer dependent on its kinase activity.